What's your agenda? Reflective supervision in community-based child welfare services. Issue 3 (4th May 2018) - Rankine, Matt; Beddoe, Liz; O'Brien, Mike; Fouché, Christa
ABSTRACT: The provision of community-based child welfare services (CCW) in a managerialist climate in Aotearoa New Zealand (ANZ) necessitates constantly renegotiated contractual partnerships, service targeting and measured outcomes. Reflective supervision is essential to counter the perceived negative impacts of managerialism on CCW work. Within this environment, there is a struggle to ensure supervision provides reflective spaces for social workers to develop in their work with service users despite the demands of meeting organisational imperatives. This article reports on a qualitative study which critically analyses the espoused theory and theories-in-use [Argyris, C., & Schön, D. (1974). Theory in practice: Increasing professional effectiveness . San Francisco, CA: Jossey Bass.] about reflective supervision held by social workers practising in the demanding environment of CCW. In the first phase of the research reported here, nine key informants who had both considerable experience in CCW and academic experience in ANZ were interviewed about the nature of reflective supervision in CCW social work. Findings indicate that social workers working in CCW settings are influenced by factors associated with self-awareness, relationships, organisational and professional obligations within a changing and risk-averse managerial environment. Key informants assert that social workers from CCW backgrounds need reflective supervision to engage in self-reflection, consider wider socio-cultural factors and to critically develop social-justice-informed practice with service users.